2013
DOI: 10.1186/1471-2148-13-176
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in brown trout Salmo truttaacross the Danube, Rhine, and Elbe headwaters: a failure of the phylogeographic paradigm?

Abstract: BackgroundBrown trout Salmo trutta have been described in terms of five major mtDNA lineages, four of which correspond to major ocean basins, and one, according to some authors, to a distinct taxon, marbled trout Salmo marmoratus. The Atlantic and Danubian lineages of brown trout meet in a poorly documented contact zone in Central Europe. The natural versus human mediated origin of the Atlantic lineage in the upper Danube is a question of both theoretical and practical importance with respect to conservation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 49 publications
(58 reference statements)
0
40
0
Order By: Relevance
“…Whereas some tissue samples are identical to those used in Lerceteau-Köhler et al (2013), sample sizes were increased in 2012 and 2013 using non-invasive tissue sampling during standard electrofishing monitoring, approved by the local responsible authorities. The three wild populations (Etrachbach-ETR, Lohnbach-LOH and Wolfsgrabenbach-WOL) represent the native Danubian lineage with no sign of introgression from foreign sources (Lerceteau-Köhler et al 2013;Schenekar et al 2014). Etrachbach and Wolfsgrabenbach are in the southern provinces of Austria (Styria and Carinthia), whereas Lohnbach lies in Lower Austria, a province northeast of the Alps.…”
Section: Sample Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas some tissue samples are identical to those used in Lerceteau-Köhler et al (2013), sample sizes were increased in 2012 and 2013 using non-invasive tissue sampling during standard electrofishing monitoring, approved by the local responsible authorities. The three wild populations (Etrachbach-ETR, Lohnbach-LOH and Wolfsgrabenbach-WOL) represent the native Danubian lineage with no sign of introgression from foreign sources (Lerceteau-Köhler et al 2013;Schenekar et al 2014). Etrachbach and Wolfsgrabenbach are in the southern provinces of Austria (Styria and Carinthia), whereas Lohnbach lies in Lower Austria, a province northeast of the Alps.…”
Section: Sample Populationsmentioning
confidence: 99%
“…Genetic studies on Austrian brown trout have shown that stocked hatchery fish are mainly of the Atlantic mtDNA lineage whereas limited numbers of native populations were found to consist mainly of Danubian mtDNA lineage fish (Bernatchez 2001;Lerceteau-Köhler et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, only brown trout with the Da haplotypes are considered indigenous in this region, while the occurrence of other lineages is considered a consequence of introduction (Bernatchez et al, 1992;Bernatchez, 2001;Duftner et al, 2003;Snoj, 2004;Marić et al, 2006). Although there are some disagreements about the modes of settlement of Atlantic populations in Austrian Danube drainages (Balon, 1968;Weiss et al, 2001;Lerceteau-Kohler et al, 2013), there is no evidence of the natural occurrence of this lineage south and southeast of the Alps. This is supported by the fact that Romanian rivers are exclusively inhabited by brown trout of the Danubian lineage (Popa et al, 2013).…”
mentioning
confidence: 99%
“…In addition to these, Bardakci et al (2006) proposed a seventh, the Tigris lineage, from the Tigris River basin in southeastern Anatolia. Lerceteau-Kohler et al (2013) questioned the allopatric origin of the Mediterranean lineage, suggesting the possibility of independent origin in particular (e.g., Adriatic) mtDNA lineages with respect to both their broad dispersal range and phenotypic divergence, and emphasized that brown trout of the Danubian lineage exhibit extensive life-history diversity and stretch across the entire Ponto-Caspian basin, leaving some uncertainty about where the lineage actually arose as well as its significance related to evolutionary or taxonomic debate. In Serbia and the Balkans, the most common brown trout are those of the Da mtDNA lineage.…”
mentioning
confidence: 99%